Simvastatin in vitiligo: an update with recent review of the literature. (7th February 2021) - Hasan, Rashidul; Agarwal, Komal; Podder, Indrashis; Misitzis, Angelica; Schwartz, Robert A.; Wollina, Uwe; Lotti, Torello; Grabbe, Stephan; Goldust, Mohamad
Abstract: Patients with vitiligo often seek medical attention, as it diminishes their quality of life resulting in significant morbidity. Several topical and systemic therapies are in vogue targeting the immunological aspect of this disease, but results are often unsatisfactory, and complete cure remains elusive. Recently, simvastatin, a 3‐hydroxy‐3‐methylyglutaryl‐coenzyme A (HMG‐CoA) reductase inhibitor, is being evaluated for vitiligo management because of its multimodal action, easy availability, and low cost. The proposed multimodal actions range from anti‐inflammatory, antioxidant, to immunomodulatory properties which may be of therapeutic benefit in vitiligo patients. The authors intend to evaluate the role of simvastatin as a novel therapeutic agent for vitiligo along with relevant review of literature.